ChemInform Abstract: Direct Catalytic Asymmetric Vinylogous Mannich‐Type Reaction of γ‐Butenolides with Ketimines. Issue 49 (3rd December 2013) - Yin, Liang; Takada, Hisashi; Kumagai, Naoya; Shibasaki, Masakatsu
Abstract The activation of the N‐thiophosphinoyl group by a mild Lewis acid is the key to achieve the enantioselective title reaction.